2022
DOI: 10.1126/sciadv.abm1899
|View full text |Cite
|
Sign up to set email alerts
|

A long-life lithium-oxygen battery via a molecular quenching/mediating mechanism

Abstract: The advancement of lithium-oxygen (Li-O 2 ) batteries has been hindered by challenges including low discharge capacity, poor energy efficiency, severe parasitic reactions, etc. We report an Li-O 2 battery operated via a new quenching/mediating mechanism that relies on the direct chemical reactions between a versatile molecule and superoxide radical/Li 2 O 2 . The battery exhibits a 46-fold increase in discharge capa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 62 publications
0
37
0
2
Order By: Relevance
“…6l), which indicates that the low charge voltage (3.6 V) during the cycle cannot induce the decomposition of the TEGDME electrolyte. 43–45 Comparatively, residual Li 2 O 2 (54.7 eV) can be identified on recharged Zn ZIF and Zn 0.6 Co 0.4 ZIF electrodes, indicating their poor reversibility. In addition, the formation of large amounts of LiCO 3 (55.5 eV) on recharged Zn ZIF and Zn 0.6 Co 0.4 ZIF electrodes can be attributed to the decomposition of electrolytes at high charge potential, which gives rise to the premature death of LOBs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6l), which indicates that the low charge voltage (3.6 V) during the cycle cannot induce the decomposition of the TEGDME electrolyte. 43–45 Comparatively, residual Li 2 O 2 (54.7 eV) can be identified on recharged Zn ZIF and Zn 0.6 Co 0.4 ZIF electrodes, indicating their poor reversibility. In addition, the formation of large amounts of LiCO 3 (55.5 eV) on recharged Zn ZIF and Zn 0.6 Co 0.4 ZIF electrodes can be attributed to the decomposition of electrolytes at high charge potential, which gives rise to the premature death of LOBs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[85] To overcome the electron transfer issue of traditional solidstate electrocatalysts, some soluble catalysts or redox mediators have been applied in Li-O 2 batteries to facilitate the decomposition of electronically insulating discharge products (e.g., Li 2 O 2 ) during the charge process. [86][87][88][89][90][91][92][93][94] It has been shown that heme molecules 1 m LiClO 4 in tetraethylene glycol dimethyl ether electrolytes can function as a soluble redox catalyst and oxygen shuttle agent for efficient oxygen evolution reaction in Li-O 2 batteries. As illustrated in Figure 10e, the reversible chemical and electrochemical redox center is the rapid electron transfer to/from Fe ions (Fe 3+ /Fe 2+ couple) in heme.…”
Section: Proteins As Catalystsmentioning
confidence: 99%
“…Abraham devised lithium–oxygen battery (LOB) as an energy storage device in 1996. Its high energy density at ∼3500 Wh kg –1 has pushed LOBs to the arena of the next-generation energy competition. During the discharge process of LOBs, oxygen molecules dissolved in electrolyte are reduced to superoxide radicals (O 2 – ) on air cathodes, followed by formation of lithium superoxide (LiO 2 ). One more electron is transferred to the intermediate to form lithium peroxide (Li 2 O 2 ) as the final discharge product. Two competitive pathways via surface versus solution are available for the LiO 2 -to-Li 2 O 2 conversion …”
Section: Introductionmentioning
confidence: 99%
“…Charge redox mediators (RMs) have been employed to resolve the problem of the limited peroxide decomposition . (2,2,6,6-Tetramethylpiperidin-1-yl)­oxyl or TEMPO, as a representative of the charge RMs, is oxidized into TEMPO + on the electrode surface at 3.74 V vs Li + /Li. , The TEMPO oxidation was kinetically more favored than the Li 2 O 2 oxidation even if the thermodynamic oxidation potential of Li 2 O 2 (2.96 V vs Li + /Li) was lower than that of TEMPO. Then, TEMPO + oxidizes Li 2 O 2 deposits, returning to TEMPO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation